’Pengaruh Pengeluaran pemerintah dan Penanaman Modal Asing (PMA) Terhadap PDRB Kabupaten/Kota Di Provinsi Kalimantan Barat’’ - B01112043, Sunarti (Jurnal Curvanomic, 2016)
The success of regional economic development can be measured througheconomic growth and the height of economic growth can be identified by the levelof Gross Regional Domestic Product (GRDP). This study aimed to analyze theeffect of government expenditure and Foreign Direct Investment (FDI) on theGross Regional Domestic Product (GRDP) of districts and cities in WestKalimantan. This research employed descriptive quantitative with multiple linearregression models. Coefficient test determination (R2), F test and t test wereutilized to test the hypothesis.The findings indicate thet government expenditure has positive andinsignificant effect toward the GRDP of district and cities in West Kalimantanwith score 0,010325 meanwhile Foreign Direct Investment (FDI) encompassespositive and significant effect on district and cities in West Kalimantan with score0,081154. The result also designate that the score of determination coefficient is0,995631. This score shows that variable of government expenditure and variableof Foreign Direct Investment can 99,56% illuminate the variable of GrossRegional Domestic Product and other variables including domestic directinvestment, labor, consumption, number of inhabitants and other excludedvariables in this model is able to 0,44% elucidate the variable of Gross RegionalDomestic Product.Keywords: government expenditure, Foreign Direct Investment (FDI), GrossRegional Domestic Product (GRDP)